(untitled) (Modern education and development, 2025)
This article analyzes the types of economic agents and their applications in economic processes. Economic agents are consumers, producers, financial institutions, the state and other economic entities, each of which plays an important role in the economic system. Consumers form demand, producers form supply, and financial institutions play an important role in the allocation of resources. The state regulates the market through economic policy and ensures social stability.